Developing Test Performance Communication Solutions in a Teacher-Researcher Partnership. Issue 3 (3rd July 2022) - Gotch, Chad M.; Roduta Roberts, Mary
ABSTRACT: Individual-level score reports represent a common artifact in teacher-parent communication about standardized tests. Previous research has documented challenges in communicating student achievement. Researchers have also leveraged teachers in the process of score report design. Little is known, however, about teachers' experiences with using score reports in authentic settings. In this study, we used a participatory action research approach in a year-long clinical partnership with four elementary teachers to iteratively propose and assess tools and strategies to support the communication of student test performance. Teachers achieved some success in their efforts, but experienced challenges of sustainability and anticipated peer buy-in. Findings from this study also illustrated a strong presence of tensions in the teachers' work related to testing and communicating test performance. Overall, involving teachers in participatory research inquiry yielded novel insights for extending score report research and improving operational practice in test companies.